The Malaysian Workplace Bullying Index (MWBI): A new measure of workplace bullying in Eastern countries - Sam, Sharon Mee Kwan; Michelle R. Tuckey; Maureen F. Dollard (2020)
Workplace bullying is a significant cause of stress at work. Existing studies, primarily based on Western-oriented frameworks and instruments, have largely overlooked the role of culture. This oversight questions whether understandings generated from those studies can be generalised to employees working in Eastern countries, which differ on important cultural dimensions. To date, there is no Eastern-based instrument for measuring workplace bullying. In two studies, we developed and validated such a measure: the Malaysian Workplace Bullying Index (MWBI). Study 1 entailed a content validation of bullying behaviours via written records (diaries) completed by Malaysian bullying victims. The 19 validated behaviours formed the basis of Study 2, with additions from the wider literature. Study 2 used survey data collected at three time-points from Malaysian employees exposed to bullying at work. The final result was an 18-item scale with two nine-item factors: work-related bullying and person-related bullying. Overall, the MWBI is a psychometrically sound measure of workplace bullying in Eastern workplaces.